Psychological sporting talent and indicators of mental health at young male and female handball players - Paušek, K.; Paušek, D.; Sertic, D.; Missoni, S.; Sindik, J. (Sports Science and Health, 2017)
The main goal of the research is to determine gender differences in the subscales within Multidimensional Scale of Sports` Psychological Talents (MSSPT): Mental Energy Scale (MES), Modified Big Five Inventory (MBFI), Modified Short Hardiness Scale (MSHS), Modified Athletic Engagement Scale (MAES), Modified Athletic Identity Scale (MAIS), Psychological Skills Inventory for Sports (MPSIS) and Modified Optimism Scale (OS)-R. The samples of 105 male (M) and 54 female (F) handball players were examined (age range 12-16 years), members of the teams Prvo plinarsko društvo, Metalac (Zagreb) and Zamet (Rijeka) (M); Zamet (Rijeka) and Samobor (F), in the beginning of 2015. The results revealed that six statistically significant gender differences are found: enthusiasm and motivation (higher means for females), extraversion, resilience, self-confidence and concentration (higher means for males). The results provide the information about possible differentiated approach of the coaches when working with male and female handball players.